Identifying the Entrepreneurship Behavioral Dimension of Tribal Dairy Farmers in Balrampur District of Chhattisgarh - Gupta, Ravi Kumar; Saha, Anindita; Tiwari, Pravin Kumar (Indian Journal of Extension Education, 2021)
Dairy farming is not an essential part of farming but also the most appropriate productive system, with enormous potential for improving the socio-economic status of dairy farmers in the tribal region. The study was conducted during 2018-19 in the Northern Hill Region of Chhattisgarh to identify the dimension of entrepreneurial behaviour of tribal dairy farmers with the help of Principal Component Analysis (PCA). It extracted the important information to display the pattern of similarity between the observations from the statistical data of tribal dairy farmers and to represent the new set of orthogonal variables as risk-bearing ability, level of interest, level of confidence, managerial ability, innovativeness, motivation, optimistic attitude, and risk respectively.
Keywords: Dairy farming; Entrepreneurial behaviour; Milk production; Principal component analysis; Socio-economic status; Tribal; Dairy farmers